PENGARUH TINGKAT SUKU BUNGA, NILAI TUKAR, PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Kharisma Sakin; Diah Nurdiawaty; Sugeng (Cahaya Ilmu Bangsa, 2025)
This study is based on theoretical problems and aims to determine and understand the inconsistencies regarding the dynamics of the relationship between interest rates, exchange rates, and Price Earning Ratio (PER) and stock prices in the banking sector listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period, both simultaneously and partially. This study uses a quantitative method using data on independent variables of interest rates, exchange rates, and Price Earning Ratio (PER), while the dependent variable in this study is stock prices. Sample determination uses a purposive sampling technique. The data analysis techniques used are classical assumption tests, multiple linear regressions, and hypothesis tests using SPSS 23.00. The results of this study indicate that partially interest rates and exchange rates have a significant effect on stock prices. While the Price Earning Ratio partially has no significant effect on stock prices. And simultaneously interest rates, exchange rates, and price earning ratios have a significant effect on stock prices. For further researchers who will conduct research on the same topic as this study, it is better to add other factors that can also affect stock prices, such as inflation, PBV so that they can develop this study. The number of samples should also be increased in further research so that the sample can better represent the population studied. This study is expected to be a reference for further researchers.